(untitled) (Rasividya : Jurnal Pendidikan, 2025)
The aim to be achieved in general in this research is to provide a clearer understanding of the Ngejot tradition between Hindu society and Islamic society, and specifically in this research is to answer the three problem formulations that have been formulated, namely: (l) To find out the implementation Ngejot tradition between the Hindu community and the Islamic community in Atula Village, Ladongi District, East Kolaka Regency, Southeast Sulawesi Province, (2) To find out what social religious values are contained in the Ngejot tradition between the Hindu community and the Islamic community in the Village Atula, Ladongi District, East Kolaka Regency, Southeast Sulawesi Province, (3) To find out the meaning of the Ngejot tradition between the Hindu community and the Islamic community in Atula Village, Ladongi District, East Kolaka Regency, Southeast Sulawesi Province. From the data analysis process, results were obtained (l) Ngejot traditions between Hindu communities and Islamic communities, including: history of Ngejot, implementation of Ngejot, function of Ngejot. (2) socio-religious values in the Ngejot tradition between Hindu and Islamic communities, including: the value of harmony, tolerance, ethical values, and (3) the meaning of the Ngejot tradition between Hindu and Islamic communities, including: the meaning of togetherness, the meaning of peace, the meaning of mutual respect, and the meaning of deliberation